Evaluation of enzyme-linked immunoelectrotransfer blot for diagnosis of cysticercosis in swine from North India. Issue 5 (16th July 2018) - Gupta, K.K.; Singh, A.; Singh, A.K.; Singh, S.K.; Tripathi, M.; Gupta, R.K.; Prasad, K.N.
Abstract: Taenia solium cysticercosis is a major public health problem in developing countries. Swine cysticercosis results in economic losses for pig farmers in disease endemic areas. Consumption of cysticercotic pork leads to taeniasis in humans. Eggs excreted in the faeces of T. solium carriers disseminate to humans and pigs through the faecal–oral route, thus maintaining the life cycle in endemic areas. An enzyme-linked immunoelectrotransfer blot (EITB) assay was developed using whole crude T. solium cysticercus antigens (WCA) for the diagnosis of swine cysticercosis. Sera from 30 swine with cysticercosis confirmed by magnetic resonance imaging were subjected to EITB assay. Sera from 50 swine that were raised in a government farm and not allowed to roam freely were included as negative controls. Two or more bands of 8, 11, 14, 24, 26 and 29 kDa were immunoreactive on blot with sera from all infected swine except two, and none from swine raised on the government farm. The overall sensitivity and specificity of EITB assay for diagnosis of swine cysticercosis were 93.3% and 100%, respectively. Hence, EITB assay based on WCA may be a suitable diagnostic tool for swine cysticercosis in endemic areas.